EFL teachers' beliefs/practices correspondence in reading instruction: does language teacher education make a difference?. Issue 1 (2nd January 2016) - Karimi, Mohammad Nabi; Dehghani, Asieh
Abstract: The present study examined EFL teachers' theoretical orientations towards reading, their reading instructional practices and the correspondence between the theoretical orientations/practices. The study participants were 80 male and female Iranian EFL teachers teaching at a number of private English language institutes. Half of the teachers were certified BA and MA holders of TEFL while 40 others were practicing teachers without TEFL-related certification. Teachers' Orientation to Reading Instruction (TORI) was used to measure the teachers' theoretical orientations towards reading instruction. There were also class observations of 25% of the surveyed teachers to explore the correspondence or lack thereof between their professed theoretical orientations towards reading instruction and their actual reading instructional practices. A series of independent samples t -tests and Pearson product-moment correlation procedures were run to analyze the data. The results showed no significant difference between the two groups of teachers in their orientations towards reading instruction. However, there were significant differences between the two groups in their instructional practices. The results further confirmed a low correlation between self-reported theoretical orientations and actual reading instructional practices among the uncertified group of teachers and a high correlation between the certified teachers' self-reported theoretical orientations to reading instruction and their reading instructional practices.